Prevalência e fatores associados ao uso de fotoprotetor no sul do Brasil: um estudo de base populacional. - Duquia, Rodrigo Pereira (2006)
Background: Sunscreen use is important for the prevention of skin cancer, but population-based information about the prevalence and its associated factors are scarce in Brazil. Objective: To evaluate the prevalence and associated factors with sunscreen use among Brazilian adults. Methods: We conducted a cross-sectional population-based study with a representative sample of adults aged 20 years or older living in the urban area of the city of Pelotas, Southern Brazil. We evaluated sunscreen use at the beach, at work, and during outdoor sports, for at least 20 minutes between 10 a.m. and 4 p.m., from December 2004 to March 2005. The outcome measure was dichotomized in subjects who never used sunscreen, and those who used sunscreen, regardless of frequency. Results: Prevalence of sunscreen use at the beach, work, and outdoor sports was 60.8% (CI95% 55.6 - 66.0), 13.7% (CI95% 10.7 - 16.6%), and 30.2% (CI95% 24.1 - 36.3), respectively. At work, the median number of days of exposure was 70 days, while at the beach it was 10 and, for sport it was 16. Females, whites, those with higher educational achievement, and with higher income were more likely to use sunscreen. Limitations: No data on adequacy of sunscreen use was gathered Conclusion: Our data show that the subjects most exposed to sunlight are those that use sunscreen the least. Interventions targeting this group are required, since this is also the population with the lowest socioeconomic level.